The evolution of the discourse of a Belgian fair trade organization: a two-dimensional history. Issue 1 (3rd May 2016) - Geysmans, Robbe
Abstract : Purpose: This paper aims to provide a detailed account of the evolution of the fair trade discourse of a Belgian fair trade organization, with a specific focus on the changes in the combination of the organization's trade and social (movement) dimensions. Design/methodology/approach: This study is based on an analysis of the organization's discourse as found in the member magazine at four periods. These four periods cover different phases in the life history of the organization and in the broader fair trade field. Findings: Throughout the organization's history, both social (movement) and trade dimensions know drastic changes, also in their mutual relationship. In the earliest history, trade practices are clearly subordinate to goals of a socialist-inspired societal change, while in the more recent history, trade has permeated the entire discourse, putting the trade dimension in a more central position. However, both dimensions seem to evolve in a connected way, as the discourse shows clear similarities on both, and evolutions can be related to changes in the organization's broader field. Originality/value: Focusing on the discourse of a specific fair trade organization breaks with a tradition of broad notions of a fair trade history. Moreover, this case provides insight into the evolution of the mix of both social and economic dimensions within a specific organization, and connects this to evolutions in the broader (fair trade) field.